(untitled) (Journal of Medicine, 2017)
Introduction: Enteric fever is highly prevalent in Bangladesh. Multidrug resistant salmonella Typhi is emerging throughout the world as well as in Bangladesh. Observing recent sensitivity pattern will help in choosing proper empirical antibiotics in resource limited country like Bangladesh as culture facilities is not available throughout the country. Materials and Methods: The study included 86 S. typhi isolates from blood cultures of patients suffering from suspected typhoid fever who attended the outpatient clinics or were admitted in Islami Bank hospital in Dhaka during January 2015 to July 2017. Results: A total of 86 S. typhi isolates were included in the study. Mean age of the study population was 22.06±17.1 and there was male 44 (51.2%) predominance. All the isolates of S. typhi were sensitive to Meropenem. Highest resistance was observed against Amikacin (62.4%) closely followed by Co-timoxazole (48.4%) and Amoxiclav (46.5%). The S. typhi isolates showed low-level resistance against Ceftriaxone (1.16%), Cefuroxime (4.6%), Azithromycin(13.9%), Levofloxacin (11.6%). Conclusions: According to findings of this study it can be advised that oral form of Cefuroxime, Levofloxacin and Azithromycin can be used as a first line. Then if patient is nonresponsive Ceftriaxone might be used. Meropeman should be reserved for selective cases. J MEDICINE Jan 2018; 19 (1) : 15-17